2010
DOI: 10.2135/cropsci2009.07.0400
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress during Late Vegetative Growth of Maize: Effects on Phenology and Assessment of Optimum Temperature

Abstract: Prediction of phenology is based on thermal time (TT) computation, which requires the correct definition of base (TB) and optimum (TO) temperatures. Most information on these traits came from controlled environments using a wide range of mean air temperatures (TX), including TX > TO and TX < TB These conditions are rarely found in field environments. We assessed the effect on development of day‐time temperatures above TO during late‐vegetative growth of maize (Zea mays L), and established a model based on TT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 34 publications
6
53
0
1
Order By: Relevance
“…Previous studies report inhibition due to heat stress in growth and yield of rice (Jagadish et al 2007;Mohammed and Tarpley 2009) and maize (Karim et al 2001, Crafts-Brandner andSalvucci 2002;Sinsawat et al 2004;Cicchino et al 2010). To the best of our knowledge, there is no report about the comparative response of maize and rice to similar degree of high temperature that would indicate their relative sensitivity to heat stress, if any.…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies report inhibition due to heat stress in growth and yield of rice (Jagadish et al 2007;Mohammed and Tarpley 2009) and maize (Karim et al 2001, Crafts-Brandner andSalvucci 2002;Sinsawat et al 2004;Cicchino et al 2010). To the best of our knowledge, there is no report about the comparative response of maize and rice to similar degree of high temperature that would indicate their relative sensitivity to heat stress, if any.…”
Section: Introductionmentioning
confidence: 91%
“…Heat stress reduced maize grain weight due to proportional losses in grain composition (starch, protein and oil contents) and due to its direct effect during the grain-filling period, which caused a cessation of grain filling (43)(44) . Moreover, heat stress reduced maize grain yield due to its negative effect on plant growth and development by increasing the abortion of fertilized structures (45,46) . The differences observed among hybrids on grain and corn ear yield was due to the timing of male and female flowering and individual weight of the corncob and grain.…”
Section: Discussionmentioning
confidence: 99%
“…The heat stress reduction factor using T can performed better than that using T air when the critical threshold temperature determined in Cicchino et al (2010a) was used.…”
Section: Discussionmentioning
confidence: 95%
“…Rattalino Edreira et al (2011,2012,2013) indicated that reduction in yield is explained by both a reduction in RUE (-3 to 33 % of Another aspect of crop growth and development known to be affected by high temperatures is phenology. Thus, there is evidence to suggest that high temperatures delay flowering (Cicchino et al, 2010a …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation